Honey: food or medicine? - Saba ZH; Suzana M; Yasmin Anum MY (Penerbit UKM, 2013)
Honey is a natural substance produced by honeybees, Apis mellifera, from the nectar of blossomed flowers or exudates of trees and plants producing nectar honeys or honeydews, respectively. It is a supersaturated solution of sugars, enriched with proteins, minerals, vitamins, organic acids and polyphenols. Honey possesses numerous nutritional, healing and prophylactic properties attributed by the rich components found in honey. Some of the health beneficial properties include wound healing, antimicrobial, antioxidant and anti-inflammatory potential. This review relates the nutritional composition, antioxidant and therapeutical effects of honey with emphasis on Malaysian honeys.